Implementation of logistics information system to support reverse logistics: a case study. Issue 1 (15th November 2004) - Lau, H.C.W.; Lee, C.K.M.; Choy, K.L.; Ip, W.H.; Chan, F.T.S.; Ip, R.W.L.
The carrying back of goods sold to the market has grown to be an important area of the logistics system for manufacturers today. Increased concern for the environment has led to new techniques to design products and supply chains that are both economically and ecologically feasible. The aim of this paper is to propose an infrastructure framework for supporting the design and implementation of a reverse logistics system. The first target is using the reverse logistics infrastructural framework to minimise the total logistics cost. The company should not only count the cost of forward logistics in terms of pushing the goods to the market, but also take into consideration the cost of taking the goods back to the point of origin. The second target is to set up the relevant information management tools to execute the reverse logistics activities at the minimum cost of additional expenses of the company. To validate the feasibility of the approach, a case study on a telecommunications services supply company has been conducted with promising results.